2021
DOI: 10.3389/fonc.2021.711225
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current In Silico Methods for Repositioning Drugs and Chemical Compounds

Abstract: Drug repositioning is a new way of applying the existing therapeutics to new disease indications. Due to the exorbitant cost and high failure rate in developing new drugs, the continued use of existing drugs for treatment, especially anti-tumor drugs, has become a widespread practice. With the assistance of high-throughput sequencing techniques, many efficient methods have been proposed and applied in drug repositioning and individualized tumor treatment. Current computational methods for repositioning drugs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…The present approach integrates QSAR and IVIVE and will contribute to other areas of research, such as drug repositioning, which recently attracted attentions towards pharmaceuticals that are available on the market and might be repurposed for new diseases (Jourdan et al, 2020). However, the previously proposed methodologies (Iwata et al, 2018; Lippmann et al, 2018; Zhu et al, 2020; He et al, 2021) have a room for improving the IVIVE aspect of in vivo prediction. Thus, our system provides an alternative to screen candidate drugs and explore new biologically similar drugs at a low cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present approach integrates QSAR and IVIVE and will contribute to other areas of research, such as drug repositioning, which recently attracted attentions towards pharmaceuticals that are available on the market and might be repurposed for new diseases (Jourdan et al, 2020). However, the previously proposed methodologies (Iwata et al, 2018; Lippmann et al, 2018; Zhu et al, 2020; He et al, 2021) have a room for improving the IVIVE aspect of in vivo prediction. Thus, our system provides an alternative to screen candidate drugs and explore new biologically similar drugs at a low cost.…”
Section: Discussionmentioning
confidence: 99%
“…However, the previously proposed methodologies (Iwata et al, 2018;Lippmann et al, 2018;Zhu et al, 2020;He et al, 2021) have a room for improving the IVIVE aspect of in vivo prediction. Thus, our system provides an alternative to screen candidate drugs and explore new biologically similar drugs at a low cost.…”
Section: Discussionmentioning
confidence: 99%
“…The present approach integrates QSAR and IVIVE and will contribute to other areas of research, such as drug repositioning, which has recently attracted attention toward pharmaceuticals that are available on the market and might be repurposed for new diseases (Jourdan et al, 2020). However, the previously proposed methodologies (Iwata et al, 2018;Lippmann et al, 2018;Zhu et al, 2020;He et al, 2021) have room for improving the IVIVE aspect of in vivo predictions. Thus, our system provides an Pros.…”
Section: Discussionmentioning
confidence: 99%
“…Drug repositioning approaches assist in minimizing the cost and time of the drug development process due to their known efficacy and therapeutic potential against other diseases . There are various computational methods such as feature-based methods, matrix decomposition-based methods, network-based methods, and reverse transcriptome-based methods for drug repositioning. , However, it has been observed that drug development efforts for the treatment of Ewing sarcoma (ES) have been largely unsuccessful in the last decade …”
Section: Introductionmentioning
confidence: 99%
“…2 There are various computational methods such as feature-based methods, matrix decomposition-based methods, network-based methods, and reverse transcriptome-based methods for drug repositioning. 3,4 However, it has been observed that drug development efforts for the treatment of Ewing sarcoma (ES) have been largely unsuccessful in the last decade. 5 ES is a cancerous tumor usually observed in bones and other soft tissues like cartilages and nerve tissues, respectively.…”
Section: Introductionmentioning
confidence: 99%